Comparison of The Effectiveness of Cleaning Products Herbal Ingredients Against the Growth of Candida albicans - Megawati, Megawati; AR, Nurul Izza; Risqika, Risqika (Politeknik Sandi Karsa, 2022)
Leukorrhea is a symptom that arises from vaginitis. This disease is mostly caused by Candida infections, especially Candida albicans. This disease causes an uncomfortable feeling for the sufferer. for that, we need to maintain the balance of the vaginal ecosystem. The aim of the research was to find out the Comparison of the Effectiveness of the Inhibitory Power of Feminine Cleansing Products Made from Herbs on the Growth of Candida albicans. This type of research was carried out experimentally, which is a laboratory study using a simple experimental design. The research was conducted in October 2022 at the Microbiology Laboratory of the Pharmacy Department of the Sandi Karsa Polytechnic Makassar. Based on the results of the research conducted, it can be concluded that the effectiveness of the inhibition of feminine products in Sample I was stronger in inhibiting the growth of Candida albicans compared to Sample II.